Estrutura e apropriação de espécies lenhosas de mangue no Delta do Parnaíba, Nordeste do Brasil. - Meireles, Victor de Jesus Silva (2016)
The mangrove has a historical relationship with fishing communities, providing many features that ensured them their livelihood. The study of the interrelationship between these traditional communities and natural resources is extremely important for conservation of local biodiversity. We evaluate the traditional extraction of mangrove species in the Canarias Island / MA, Brazil Northeast, particularly regarding the collection of wood products, identifying the factors that influence this process. Therefore, we used techniques applied in ethnobotany and Phytosociologial. After conducting a direct observation, applied semi-structured interviews with 100 fishermen on the use of the mangrove species. Later, they were selected through informal conversations key informants of the survey (n = 12), who applied more specific forms of such use, participatory mapping techniques and field tours, aimed at confirmation of species and determination of areas of resource extraction. The importance of the species was determined by the number of citations, index of Use Value (VU) Relative Importance (IR), Relative Frequency (RF) and Importance Value Index (IVI). The categories had their importance measured by the number of citations and by the Informant Consensus Factor Index (FCI). The availability of the species was obtained by the structural analysis of two areas with different levels of human use. It enrolled 134 individuals belonging to three botanical families (Acanthaceae, Combretaceae and Rhizophoraceae). Considering the timber use, the species were distributed in categories: technology (16 citations), fuel (n = 6) and construction (n = 43), the last presented greater local importance (FCI = 0.98). The most important mining areas were ?Igarapé dos Poldros?, "Pontal" and ?Lagoa Salgada?. The species most important timber utility were R. mangle (VU = 1.26) and A. germinans (VU = 0.21) and is the most relevant considering the availability within the framework of the analyzed woods with IVI = 300 00 and IVI = 188.45, respectively, which corroborates the Hypothesis of Ecological Appearance (HAE). However, the collection of R. mangle can is being influenced by the risk of foraging. Whereas the medicinal use, the kind of place most importance was the R. mangle, highlighting in number of citations (n = 48), Use Value (VU = 1.23) Relative Importance (IR = 2, 00) and Relative Frequency (RF = 86.05). The categories of greater local importance diseases were: Disorders of the circulatory system disorders not defined and disorders of the digestive system. Found, the human action in addition, other factors that exert influences on the possible structure of analyzed sites, such as salinity, concentration of aluminum available flood level. It is noticed that the analyzed anglers have a varied area for its medicinal and timber use, due to the interrelationship relationship with this environment, built over generations. The use of woody species of mangrove forests, as well as knowledge associated with these, should be an integral part d the area conservation process.